Positive Association of Metabolic Syndrome with a Single Nucleotide Polymorphism of Syndecan-3 (rs2282440) in the Taiwanese Population - Betty Chia-Chen Chang; Lee-Ching Hwang; Wei-Hsin Huang (International Journal of Endocrinology)
Background/Purpose. Metabolic syndrome (MetS) poses a major public health burden on the general population worldwide. Syndecan-3 (SDC3), a heparin sulfate proteoglycan, had been found by previous studies to be linked with energy balance and obesity, but its association with MetS is not known. The objective of this study is to investigate whether SDC3 polymorphism (rs2282440) is associated with MetS in the Taiwanese population. Methods. Genotypes of SDC3 polymorphism (rs2282440) were analyzed in 545 Taiwanese adult subjects, of which 154 subjects had MetS. Results. Subjects with SDC3 rs2282440 TT homozygote had higher frequency of MetS than those with CC or CT genotype (p=0.0217). SDC3 rs2282440 TT homozygote had a 1.96-fold risk of being obese and 1.8-fold risk of having MetS (with CC genotype as reference). As for the individual components of MetS, subjects with SDC3 rs2282440 TT homozygote were more likely to have large waist circumference and low high-density lipoprotein cholesterol (OR = 1.75 and OR = 1.84, resp.). Conclusion. SDC3 rs2282440 polymorphism is positively associated with MetS in the Taiwanese population. Further investigation is needed to see if this association is mediated by mere adiposity or SDC3 polymorphism is also linked with other components of MetS such as lipid metabolism.